Are Teachers Ready? A Study on Digital Assessment Implementation - Nunung Nurhayati; Iyan Hayani; Sarah Rahmawati (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2026)
This study aims to investigate teacher readiness, perceived benefits, and challenges in implementing digital assessment across five domains: knowledge, skills, perception, facilities and support, and practical implementation. Using a mixed-method design, questionnaire data were collected from teachers (N = 112) and complemented by semi-structured interviews with certain participants to enrich interpretation. The result revealed that teachers hold positive views of digital assessment as efficient, transparent, and motivating for students. However, the actual practices are still restricted, with digital technologies primarily utilized for summative assessments and focused on simple platforms like Google Forms and Kahoot. A number of systemic limitations, such as poor infrastructure, unequal digital competency, reliance on students' gadgets, and worries about academic dishonesty, were also uncovered via interview data. Teachers' capacity to employ digital evaluation for formative or learning-oriented goals is limited by these limitations. With the findings, it highlights the necessity for continuous professional development, improved infrastructure, and clear institutional policies to support effective and ethical digital assessment practices. Future studies could explore long-term impacts and examine specific platforms to enhance teacher readiness and instructional outcomes.